Assessing customer satisfaction and financial performance to establish TH KPI’S for selecting Hajj pilgrim organizers / Abu Shukor Jangga, Abd Latif Ahmad and Mohd Hafiz Bakar - Jangga, Abu Shukor; Ahmad, Abd Latif; Bakar, Mohd Hafiz (2013)
Lembaga Tabung Haji (TH) is highly determined to provide excellent and comprehensive services with premium quality to satisfy the pilgrims need prior, during and after their pilgrimage. This is evidence of TH’s commitment and dedication, not only as an alternative entity in managing Muslims investments that are done in accordance to the Islamic teaching. TH had done whatever it supposed to take in order to meet the customer satisfaction towards their service. As the number of pilgrims increases every year, TH continues to strive to enhance its facilities and services. In order to fulfill the demand for the Hajj, TH has selected several companies to be the providers for the pilgrimage. As the quota given by the Saudi Arabia, Malaysia is given total number of pilgrims for 28,000. From that 8,000 pilgrims out of 28,000 will used the package offer by the hajj provider. Every year TH will outsource the quota to the hajj provider. The provider will provide the services based on the package they are provide. The hajj providers’ package is for those who have the capabilities in terms of money and want to perform hajj without need to wait their waiting list. The range of the package is between RM 25,000.00 to RM 40,000.00. The purposes of this study is designed to explore the level of customer satisfaction towards the service quality provided by hajj organizers and their financial performance as the determination for the Key Performance Indicator (KPI) used by TH. In order to fulfill the objective, under research methodology, the research design must be chose appropriately and what types of data were used. For the data collections; the research target population, its sampling frame and sampling procedures, data collection methods were presented. Then this chapter is concluded by the data analyses techniques and procedures used in the study. This study was conducted by distributed questionnaire to the hajj pilgrims; for primary data. The probability sampling has been used in this study and the technique using simple random sampling method. Results from the findings interpret that customer satisfaction index (CSI) was the most important elements in selecting the hajj organizers. Increased in CSI will increased the customer loyalty and it will lead to increase in profitability. Serious effort should be initiated whereby TH should set up a team and continuous research on the CSI of the hajj pilgrim via hajj organizer package should be conducted.